2019
DOI: 10.18553/jmcp.2019.25.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Economic Outcomes Associated with Safety Interventions by a Pharmacist-Adjudicated Prior Authorization Consult Service

Abstract: BACKGROUND: The establishment of a formulary management system ensures that health care professionals work together in an integrated patient care process to promote clinically sound, safe, and cost-effective medication therapy. Pharmacists have a foundational role within this system. A pharmacist-adjudicated prior authorization drug request (PADR) consult service has the potential to optimize drug therapy by decreasing medication misuse, minimizing adverse drug events (ADEs), and preventing medication errors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Data show that these techniques can save patients hundreds of dollars each year through generic and therapeutic substitution [ 30 ]. Drug utilization management is also associated with reductions in adverse drug events and improved safety and outcomes for patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data show that these techniques can save patients hundreds of dollars each year through generic and therapeutic substitution [ 30 ]. Drug utilization management is also associated with reductions in adverse drug events and improved safety and outcomes for patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…By encouraging generic and therapeutic substitution, these techniques can save patients hundreds of dollars each year [ 18 ]. Studies have also shown that it can reduce the number of adverse drug events and improve safety and outcomes for patients [ 19 ]. However, although drug utilization management is designed to ensure patient safety and the use of cost-effective medicines, it does impact physician practices.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also assessed the cost savings association with using less expensive drugs, promoting generic or biosimilar drugs, substituting parenteral drugs for oral forms, optimizing treatment duration, and enhancing medication management [ 20 29 ]. Additionally, studies measured cost avoidance through pharmacist-led interventions, such as patient-tailored activities to improve adherence or optimize drug therapy on wards [ 9 , 20 23 , 30 42 ].…”
Section: Introductionmentioning
confidence: 99%